A Non-parametric Approach In Measuring The Variances Of Compliance Levels Of Goodwill Impairment Testing - Tran Manh Dung; Khairil Faizal Khairi; Nur Hidayah Laili (Foreign Trade University, 2024)
Volume: 69 (page: 56-75)